The Effect of Double-Loop Problem-Solving Models on Students' Critical Thinking Ability - H. Halimah; S. Sutrio; Ni Nyoman Sri Putu Verawati (IKIP Mataram, 2019)
This study aims to determine the effect of double loop problem-solving models on students' critical thinking ability. The quasi-experiment with untreated control-group design with the pretest-posttest design is used. The population includes all off students in class X MIA SMAN 2 Aikmel as many as 123 people. The sampling technique used purposive sampling, and as samples are 31 students in class X MIA 2 (experimental group) and 28 students in X MIA 3 (control group). The experimental group was treated with a double loop problem-solving model while the control loop with direct instruction learning. The instrument used was a critical thinking ability test of 10 items in which two items measured each indicator. Indicators measured, namely interpretation, analysis, evaluation, inference, and explanation. The instrument test results showed that the ten items were valid and reliable so that they could be used in research. Research hypotheses were tested using pooled variance t-test. The results of the data analysis show that tcount> ttable which means that H0 is rejected and Ha is accepted, so it can be concluded that there is an effect of double loop problem-solving models on students' critical thinking ability.